A study of the information services of the Makati City Library - Amerca, Rosario I. (2000)
The study aimed to: (1) describe the characteristics of the various user groups of the Makati City Library; (2) describe the library's present services, resources, and facilities; (3) identify the range of information needs of its users; (4) evaluate the extent to which the library's present services, resources, and facilities meet the information needs of its users, and; (5) recommend and propose measures on how the library may improve its services by developing it along the lines of a business-oriented information center. The seven user groups included in the study were businessmen, government employees, housewives, the elderly, students, and children aged 10 to 13 who were regular users of the library.